Identifikasi Golongan Senyawa Flavonoid dalam Fraksi n-butanol dari Ekstrak Metanol Buah Muda Phaleria macrocarpa - Ratna Djamil; Tri Astuti (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
Unripe fruits of Mahkota Dewa (Phaleria macrocarpa [Scheff.](Boerl) containing alkaloid, flavonoid, saponin, terpenoid, volatile oil and tannin, were extracted with methanol and partitioned by the Charaux-Paris method, with. n-butanol Identification by UV-Visible spectrophotometry showed that the flavonoid from that isolate NB-1 was chalcone with OH on 3, 4, 4' position and o-diOH on ring B, and isolate NB-II was also a chalcone with OH on 4, 2', 4' position, oxygenation on 3' and o- diOH one ring B, while isolate NB-III was a flavonol with OH on 3,5,4' position with prenil on 6, and o-diOH on ring A (6,7 or 7,8).